The Influence of Evidence on Animal Cruelty Prosecution and Case Outcomes: Results of a Survey. Issue 6 (22nd May 2019) - Lockwood, Randall; Touroo, Rachel; Olin, Jaime; Dolan, Emily
Abstract: Two hundred prosecuting attorneys completed a survey concerning priorities in taking on animal cruelty cases and the factors that help or hinder prosecuting such cases. Respondents commented on the priority given such cases. Questions also addressed specific kinds of evidence that had been used to decide whether to take on a cruelty case and were used in court. Results showed that prosecutors most frequently relied upon "traditional" sources of evidence, including detailed medical and crime scene reports and good quality photographic evidence. Other sources of forensic evidence such as DNA, computer forensics, forensic accounting, blood, and trace evidence were rarely employed. Veterinary forensic evidence, including forensic necropsies and detailed medical reports, was viewed as an important factor by a majority of prosecutors in deciding whether to accept a case for prosecution and in achieving a successful outcome, but a need for additional training for investigators was indicated.